2016
DOI: 10.1002/2015ja021057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intermittency on the anisotropy of magnetic structure functions of solar wind turbulence

Abstract: Intermittency appears to be connected with the spectral anisotropy of solar wind turbulence. We use the Local Intermittency Measure to identify and remove intermittency from the magnetic field data measured by the Ulysses spacecraft in fast solar wind. Structure functions are calculated based on the time sequences as obtained before and after removing intermittency and arranged by time scale (τ) and ΘRB (the angle between local mean magnetic field B0 and radial direction R). Thus, the scaling exponent (ξ(p, ΘR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
4
12
0
Order By: Relevance
“…In fact, they recovered spectral indices of 1.63 and 1.56 for magnetic field and velocity, respectively. A similar analysis by Pei et al (), based on the use of LIM technique (see above), confirmed the effect of intermittency on turbulence spectral anisotropy.…”
Section: On the Nature Of Intermittency Eventssupporting
confidence: 77%
“…In fact, they recovered spectral indices of 1.63 and 1.56 for magnetic field and velocity, respectively. A similar analysis by Pei et al (), based on the use of LIM technique (see above), confirmed the effect of intermittency on turbulence spectral anisotropy.…”
Section: On the Nature Of Intermittency Eventssupporting
confidence: 77%
“…3.3). The results are given for the total structure function obtained by summing together the structure functions of the three components of the magnetic field as, for example, in Pei et al (2016).…”
Section: Structure Function Analysismentioning
confidence: 99%
“…A cascade of energy could produce a power law spectrum of SAFPs. Critical balance cascade (Goldreich & Sridhar 1995;Schekochihin et al, 2009, Tessein et al, 2009 or intermittent structures (Luo et al, 2011;Pei et al, 2016;Wang et al, 2014Wang et al, , 2016 may generate the observed spectral anisotropy. However, the source region of SAFPs has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…This spectral index anisotropy of magnetic turbulence in the fast solar wind is found to last throughout the inner heliosphere from 0.3 AU to 1 AU (He et al, 2013). It is often considered as a signature of a cascade according to the critical balance theory (Goldreich & Sridhar, 1995;Schekochihin et al, 2009;Tessein et al, 2009) and may also be explained by the influence of intermittent structures on the solar wind turbulence (Luo et al, 2011;Pei et al, 2016;Wang et al, 2014Wang et al, , 2016. However, for the SAFPs found by Wang et al (2015) the power and spectral index anisotropy were not investigated.…”
Section: 1002/2017ja024422mentioning
confidence: 99%